MANAJEMAN ZAKAT DI LEMBAGA AMIL ZAKAT DOMPET UMMAT KABUPATEN SAMBAS TAHUN 2017 - Neli, Neli (El-Hayah, 2017)
Abstract :Â  This research aimed to know: (1) management of zakat in Amil Zakat Institution of Dompet Ummat in Sambas District. (2) the implications of Amil Zakat Institution of Dompet Ummat Sambas District in the development of community in Sambas as a whole. This research was a qualitative descriptive analysis research. The research was conducted at Amil Zakat Institution of Dompet Ummat in Sambas District on May to June 2017. The subjects was the Institute of Amil Zakat Dompet Ummat. The informants were the Head of Institutions, employees and muzakki. Data were collected by interview, observation and documentation. Data validity checking was done by extension of participation, persistence of observation, and examination by the source of research data. Data analysis technique was done by inductive model consisting of data collection, data reduction, data presentation, and conclusion.The results of the research showed: (1) Management of collection and distribution of zakat in Amil Zakat Institution of Dompet Ummat in Sambas Regency in planning, supervision, implementation and organization was almost already running well, only job description in each division has not been arranged. But in the distribution and management of its fund management has not implemented the appropriate management of rules and rules of shariah law yet, (2) The implication of utilization and distribution of zakat in Amil Zakat Institution of Dompet Ummat in Sambas Regency has not yet improved the welfare of society as a whole, because in the proportional division of zakat is not yet shariah. Keywords: Management, Implications